Perception towards hearing handicap amongst hearing impaired individuals and its associated factors - Mohamed, Mohd Hazmi; Ishak, Azlan Iskandar; Wan Sulaiman, Wan Aliaa; Lim, Xin En; Mohd Nasir, Siti Fatin Natasya; Abu Bakar, Saraiza (Faculty of Medicine and Health Sciences, UPM, 2023)
Individuals with hearing impairment may not inevitably have hearing handicaps. They might not be psychologically or socially bothered by the deficit in daily life. Objective: This study aims to examine the perception of hearing handicaps among individuals with hearing impairment. Methods: A cross-sectional study comprised 109 individuals with hearing impairment at the ENT clinic in Hospital Serdang. Data on sociodemographic characteristics, hearing level and Hearing Handicap Inventory for Adults (HHIA) questionnaire score were accumulated. Hearing handicaps were measured using the HHIA score. Results: Out of 109 participants, 28.4% experienced a significant hearing handicap while 44% reported no handicap. Our analysis revealed that there is no discernible link between socio-demographic factors such as age group, gender, race, educational level, and overall HHIA score, which exemplify the perception of hearing handicap. However, we did find a statistically significant connection between the degree of hearing loss and the total HHIA score (p=0.003) as well as the usage of a hearing aid and the HHIA score (p=0.042). Conclusion: Our findings indicate that the level of hearing loss and the use of hearing aids have a significant impact on how individuals perceive their hearing handicap. In contrast, socio-demographic factors do not appear to influence individuals’ perception towards hearing handicaps. We recommend a regular hearing check-up in the community to enable early detection and interventions when necessary.